Exploring respiratory enzymes from Staphylococcus aureus - Barbosa, Catarina (2022)
"Staphylococcus aureus is an opportunistic pathogen that can cause various disease patterns due to its high adaptative capacity. Many aspects of the energy metabolism and its respiratory chain system are still poorly understood. Herein, we report our study of three respiratory enzymes: Membrane potential- generating system (MpsAB) and two malate:quinone oxidoreductases (MQO). The MpsAB enzyme is a membrane complex proposed to be involved in energy conservation in S. aureus due the sequence homology of the subunit MpsA with the proton-translocation subunit NuoL of complex I from Escherichia coli. To further investigate the complex a series of expression tests were made to achieve its heterologous expression in E. coli. We also tried to optimize protein purification for biochemical studies. (...)"